Some Issues on the Concept of Guilt - Gabuzyan, Ara (Bulletin of Yerevan University C: Jurisprudence, 2021)
Issues relating to the concept of guilt are discussed in the article presented. Based on the analysis of different concepts of guilt, the author comes to the conclusion that the normative concept of guilt should be used to realize the guilt principle. According to the mentioned concept, guilt exists when a person realizes the illegality of his/her action or, if he/she does not –he/she could have realized it. Such an approach is reflected in the new RA Criminal Code, and it fully complies with the requirements of the developed countries` criminal legislations of.